Online Annexes: Running on empty. The world is gearing up for climate resilience without the money to get there - Neufeldt, Henry; Hammill, Anne; Singh, Chandni; Rubial, Maria del Pilar Bueno; Pauw, Pieter; Njuguna, Lucy; Niles, Keron; Milford, F.; Dale, Thomas; Christiansen, Lars; Chapagain, Dipesh; Canales, Nella; et al. (2025)
This online annex outlines the methodology and analytical framework used to assess adaptation progress in the 2025 Adaptation Gap Report. Specifically, the section for Chapter 3 details the processes for extracting and analyzing data from Biennial Transparency Reports (BTRs) to evaluate global adaptation implementation.